Interpretação de pronomes em português L2: efeitos de transferência? - Fiéis, Alexandra; Madeira, Ana (Revista da Associação Portuguesa de Linguística, 2018)
This study investigates how knowledge of the interpretative properties of strong object pronouns develops in L2 European Portuguese. We focus on the anaphor si, which, in biclausal domains, may take either a local or a long-distance antecedent. Previous studies have shown that L2 learners show delays in the acquisition of non-reflexive pronouns in monoclausal domains (Kim et al 2014), but not of anaphors; however, knowledge of the locality constraints on anaphors in biclausal sentences has been shown to exhibit transfer effects and develop late (Domínguez et al 2012). In this study we investigate whether the learners’ L1 influences the development of the interpretative properties of pronouns by considering two groups of learners whose L1s differ regarding long-distance binding: Spanish, where it is disallowed (Otero 1999), and Italian, where, according to Napoli (1979), it is allowed. Moreover, we investigate whether learners attain full knowledge of these properties, and, if so, whether development of this knowledge is delayed, by comparing learners at different proficiency levels (intermediate and advanced). Results of two truth-value judgement tasks indicate the presence of L1 effects in learners’ interpretation of non-reflexive pronouns, but not of si in biclausal contexts, where a local interpretation is preferred over a long-distance one. Moreover, a comparison between the intermediate and the advanced groups reveals a developmental effect in the Spanish group (but not in the Italian group), indicating that the interpretative properties of si may be fully acquired, albeit subject to delays.